THE DEVELOPMENT OF THE REGULATIONS ON GENDER BASED VIOLENCE IN ROMANIA AND SPAIN - LAVINIA MIHAELA VLADILA (Challenges of the Knowledge Society)
In this article, I will present the evolution of the regulation of gender based violence in Romania and Spain. This new theme is one of actuality, due to the situations that frequently happen in our social life. Both Romania and Spain have a high level of gender based violence, even if nowadays in our country are few statistics on this matter. But also, both countries now enjoy good legislations, which have been developed in the last 10 years.